The EU Member States’ national healthcare systems compared using the single synthetic index - Jankowiak, Maciej (Economics and Business Review, 2021)
Implementation of health protection requires effective quantitative methods of its evaluation. Assessment could be based on usage of synthetic indices which aggregate couple input variables into a single measure. In this paper, the exploitation of a new synthetic index (by the author called HAI—the Healthcare Aggregated Index) was proposed with the aim of the assessment and long-term interstate comparisons of healthcare systems of the EU countries. Using taxonomic methodology, HAI involves three variables: the number of hospital beds, the number of physicians and the public expenditures on healthcare. HAI utilisation includes dynamic interstate comparisons of national healthcare systems of the different exploitations of human, physical and financial resources. The HAI application to assessment of twenty European Union Member States’ healthcare systems revealed an effect of substitution between healthcare resources within the slight international differentiation of the health protection level and the minor dynamic of changes in time series.